The sustainability of destination of the winemaking pomace in Brazil (Research, Society and Development, 2020)
Viticulture stands out in the world economy because it is one of the larger expansion alcoholic beverage industries in the world, being in full growth in Brazil. This advance also represents an increase in waste, since about 30% of the volume of vinified grapes generates pomace. In addition, if improperly disposed, this can become an environmental and economic problem. The objective of this work was to discuss the current situation of viticulture in Brazil, with a focus on the grape pomace and the measures being taken touse as a co-product, alternatives and indications of options for the future of the sector's industries. Grape pomace has many nutrients that remain after the fruit processing such as fibers, minerals and bioactive compounds. Because of this, several alternatives have been proposed to use this residue, from utilization in fertilizers, composting or animal feed, to as raw material in the development of products for human consumption, such as in the food, pharmaceutical and cosmetic industries.